Synthesis and characterization of stable lead (II) orthophosphate nanoparticle suspensions. Issue 13 (9th November 2020) - Lytle, Darren A.; Formal, Casey; Doré, Evelyne; Muhlen, Christy; Harmon, Stephen; Williams, Daniel; Triantafyllidou, Simoni; Pham, Maily
Abstract: There is great interest in producing nanoparticles for various applications. The objective of this work was to develop a procedure for reproducibly creating stable lead (Pb) phosphate nanoparticle aqueous suspensions. A stable 5 mg/L Pb-phosphate nanoparticle "stock" suspension was synthesized via chemical precipitation of Pb and orthophosphate in water at pH 7.5 with 4.4 mg soluble PO4 /L and 7 mg C/L dissolved inorganic carbon. The stock suspension was subsequently diluted to produce stable 0.10 mg/L Pb "challenge" water suspensions without compromising the nanoparticle size, structure, mineralogy and solubility. Specifically, the hexagonal hydroxypyromorphite nanoparticles had an average diameter of 38 nm based on transmission electron microscopy analysis and an associated Pb solubility of 0.001 mg/L. The properties of the stock suspensions were not impacted by further dilutions, and the challenge water suspensions remained stable for 24 hours. In the context of drinking water, a protocol to produce such a stable Pb nanoparticle challenge water suspension would be very useful in evaluating Pb bioavailability, identifying Pb remediation strategies, and testing filter effectiveness to remove Pb from water.